2005
DOI: 10.1074/jbc.m412757200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Apoptosis Induction by IGFBP-3 Involves an Insulin-like Growth Factor-independent Nucleomitochondrial Translocation of RXRα/Nur77

Abstract: Insulin-like growth factor-binding protein-3 (IGFBP-3) induces apoptosis by its ability to bind insulin-like growth factors (IGFs) as well as its IGF-independent effects involving binding to other molecules including the retinoid X receptor-␣ (RXR␣).Here we describe that in response to IGFBP-3, the RXR␣ binding partner nuclear receptor Nur77 rapidly undergoes translocation from the nucleus to the mitochondria, initiating an apoptotic cascade resulting in caspase activation within 6 h. This translocation is a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 64 publications
4
87
0
1
Order By: Relevance
“…3A). The "colon CTC signature" included the defensin ␣ genes [defensin alpha 5 (DEFA5) and defensin alpha 6 (DEFA6)], 10 and chemokines [C-X-C motif chemokine ligand 2 (CXCL2), C-X-C motif chemokine ligand 6 (CXCL6), C-X-C motif chemokine ligand 10 (CXCL10), C-X-C motif chemokine ligand 11 (CXCL11), C-C motif chemokine ligand 5 (CCL5), and C-C motif chemokine ligand 28 (CCL28)] also were overexpressed in HT-29 cells. Finally, the Gene Set Enrichment Analysis showed that several tumorigenesis-related genes were enriched in the "colon CTC signature," such as carcinoembryonic antigen-related cell adhesion molecule 5 (CEACAM5) and carcinoembry- IL15, interleukin 15; IL1R1, interleukin 1 receptor type 1; CXCL2, C-X-C motif chemokine ligand 2; CXCL6, C-X-C motif chemokine ligand 6; CXCL10, C-X-C motif chemokine ligand 10; CXCL11, C-X-C motif chemokine ligand 11; CCL5, C-C motif chemokine ligand 5; CCL28, C-C motif chemokine ligand 28 onic antigen-related cell adhesion molecule 6 (CEACAM6), phospholipase A2 group 2A (PLA2G2A), and aldehyde dehydrogenase 3 family member A1 (ALDH3A1).…”
Section: Cellsmentioning
confidence: 99%
“…3A). The "colon CTC signature" included the defensin ␣ genes [defensin alpha 5 (DEFA5) and defensin alpha 6 (DEFA6)], 10 and chemokines [C-X-C motif chemokine ligand 2 (CXCL2), C-X-C motif chemokine ligand 6 (CXCL6), C-X-C motif chemokine ligand 10 (CXCL10), C-X-C motif chemokine ligand 11 (CXCL11), C-C motif chemokine ligand 5 (CCL5), and C-C motif chemokine ligand 28 (CCL28)] also were overexpressed in HT-29 cells. Finally, the Gene Set Enrichment Analysis showed that several tumorigenesis-related genes were enriched in the "colon CTC signature," such as carcinoembryonic antigen-related cell adhesion molecule 5 (CEACAM5) and carcinoembry- IL15, interleukin 15; IL1R1, interleukin 1 receptor type 1; CXCL2, C-X-C motif chemokine ligand 2; CXCL6, C-X-C motif chemokine ligand 6; CXCL10, C-X-C motif chemokine ligand 10; CXCL11, C-X-C motif chemokine ligand 11; CCL5, C-C motif chemokine ligand 5; CCL28, C-C motif chemokine ligand 28 onic antigen-related cell adhesion molecule 6 (CEACAM6), phospholipase A2 group 2A (PLA2G2A), and aldehyde dehydrogenase 3 family member A1 (ALDH3A1).…”
Section: Cellsmentioning
confidence: 99%
“…The concentration of IGFBP3 used here represents one of the lowest ever shown to have an in vitro effect (15,(36)(37)(38)(39)(40).…”
Section: Igfbp3-expressing Hscs Inhibit Neovascularization By Protectmentioning
confidence: 99%
“…We have previously demonstrated a new paradigm in cancer cell apoptosis, in which Nur77 is induced, then translocates from the nucleus to the mitochondria, leading to release of cytochrome c from the mitochondria (Li et al, 2000). The apoptosis-associated nuclear egress of Nur77 has been observed in cancer cells from the lung, ovary, colon, stomach and breast (Dawson et al, 2001;Holmes et al, 2002Holmes et al, , 2003Liu et al, 2002;Wu et al, 2002;Jeong et al, 2003;Kolluri et al, 2003;Wilson et al, 2003;Cao et al, 2004;Jacobs et al, 2004;Lin et al, 2004;Lee et al, 2005). Nur77 mitochondrial localization is also involved in Sindbis virus-induced apoptosis (Lee et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Nur77-dependent apoptotic process is triggered by a number of apoptosis inducers, including retinoidrelated molecule 6-[3-(1-adamantyl)-4-hydroxyphenyl]-2-naphthalenecar-boxylic acid (AHPN) (also called CD437) (Li et al, 2000) and its analogs (Li et al, 2000;Dawson et al, 2001;Holmes et al, 2002Holmes et al, , 2003Kolluri et al, 2003;Cao et al, 2004;Lin et al, 2004), etoposide (Li et al, 2000;Liu et al, 2002;Wilson et al, 2003), and insulin-like growth factor binding protein-3 (Lee et al, 2005). The importance of Nur77-dependent apoptotic pathway in mediating the anticancer activity of chemotherapeutic agents is supported by the positive correlation between Nur77 family member Nor-1 expression and survival in diffuse large B-cell lymphoma patients treated with therapeutic drugs (Shipp et al, 2002).…”
Section: Introductionmentioning
confidence: 99%